Disciplinary and Professional Trends in Social Work in the Colombian Context - Pulecio, María Otilia; Martínez Suarez, Marisol (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The Trends in Social Work presented in this document emerge from an inter-institutional research process carried out between the Corporación Universitaria Minuto de Dios - Girardot Regional Center and the Institution of Higher Education - ITFIP, with the objective of presenting an analysis of the disciplinary and professional trends towards which the training provided by the academic units that currently offer the program in the country is directed. The study was developed under a qualitative method, with a descriptive documentary research methodology, whose methodological process followed the steps suggested by the Universidad Nacional Abierta (UNA) (1985).